Single gingival recession associated with non-carious cervical lesion treated by partial restoration and coronally advanced flap with or without xenogenous collagen matrix: A randomized clinical trial evaluating the coverage procedures and restorative protocol - Mathias-Santamaria, Ingrid Fernandes [UNESP]; Silveira, Camila Augusto [UNESP]; Rossato, Amanda [UNESP]; Sampaio de Melo, Mary Anne; Bresciani, Eduardo [UNESP]; Santamaria, Mauro Pedrine [UNESP] (Wiley, 2021)
Background: Evaluate the use of collagen matrix (CM) as adjunctive to coronally advanced flap (CAF versus CAF + CM) to treat gingival recession (GR) associated with non-carious cervical lesion–combined defects (CDs). Methods: Sixty-two patients presenting 62 CDs (RT1 GR and non-carious cervical lesion (NCCLs) were randomly allocated to either CAF group (n = 31): partial restoration of the NCCL and CAF; or to CAF + CM group (n = 31): partial restoration of the NCCL and CAF associated with CM. Clinical, esthetic, patient-centered outcomes, and restorative parameters were assessed. Results: After 12 months, CD coverage were 55.2% for CAF and 54.4% for CAF + CM (P = 0.8). Recession reduction were 1.9 ± 0.8 mm for CAF and 2.0 ± 0.7 mm for CAF + CM (P = 0.6). CAF+CM resulted in higher increase in keratinized tissue (KT) width (CAF: 0.3 ± 0.7 mm; CAF + CM: 0.9 ± 0.8 mm; P = 0.004) and KT thickness gain (CAF: 0.1 ± 0.3 mm; CAF + CM: 0.7 ± 0.2 mm; P = 0.001). Both treatments presented low postoperative pain and resulted in esthetics improvements. In addition, no restoration was lost, 27.4% showed a reduction of the superficial polishing, and 8% showed marginal staining, but still clinically acceptable. Conclusion: Partial resin composite restoration (with the apical limit up to 1 mm of the estimated CEJ) and CAF alone or combined with CM are suitable for treating CDs. The use of CM provided additional benefits in terms of KT width and thickness gain. (NCT03341598).
Keywords: dental esthetics; dentin sensitivity; gingival recession; tooth abrasion; tooth cervix